Instruments of Educational Inspection (II): reports - Pérez Aguilar, José Francisco (Avances en Supervisión Educativa, 2015)
In the exercise of their duties, education inspectors have to raise attribution reports on its own initiative or at the request of the authorities of the educational authorities, as appropriate. Furthermore, these reports can be part of a process. Therefore, it is understood as administrative documents must meet the characteristics of current regulations. The inspection report should include legal and technical facts and describing proposals, if they come, in order to provide evidence to the educational authorities to take decisions on the procedures to be resolved analysis. In its development, apply and use tools and inspectors to gather evidence supporting the valuations included techniques. In this article a brief analysis of the reports is carried out, setting them within the administrative documents, defining and analyzing its characteristics and functions. Here are some definitions and a possible classification, ending with a brief discussion of style and structure inspection reports are studied. The key is to provide elements of judgment to educational authorities to take those decisions are made. Such elements should be based on technical assessments of an inspector who is skilled in both legal and pedagogical and didactic education.